The Role of Headmaster Managerial to Create A Healthy School (Case Study at Senior High School of Muhammadiyah Sambas) - Aan Buchori; Uray Husna Asmara; Aswandi Aswandi (JETL (Journal of Education, Teaching and Learning), 2018)
This study aims to 1) find out more in depth, describe and analyze the headmaster's planning in creating a healthy school; 2) knowing more deeply, describing and analyzing the organization of headmasters in creating healthy schools; 3) knowing more deeply, describing and analyzing the direction of the headmaster in creating a healthy school; and 4) knowing more deeply, describing and analyzing the controls carried out by the Head of Senior High School of Muhammadiyah Sambas on activities to create a healthy school. This type of research is descriptive qualitative. The results of the research show that the role of the Headmaster in making healthy school planning is good enough to convince all school residents about the importance of a clean and healthy life. For the sake of the realization of a healthy school, the headmaster and the teacher council have formulated a school vision that is to realize intelligent, devoted and environmentally sound human beings. Regarding organizing, the role of the headmaster is quite democratic by involving all school residents in forming a healthy school implementation team so that the team's performance runs synergistically and simultaneously. In the implementation of the healthy school program, the school headmaster together with all the school members who were motivated by the head of the implementing team of the healthy school had implemented this program with total enthusiasm and responsibility. Supervision of healthy school programs routinely carried out by headmasters is evidenced by the growing awareness of clean and healthy lives of students, teachers, TU staff and other school residents and the community around the school.